Disability, health, law, & bioethics - Cohen, I. Glenn 1978-; Shachar, Carmel 1985-; Silvers, Anita 1940-2019; Stein, Michael Ashley (Cambridge University Press, 2020)
Historically and across societies people with disabilities have been stigmatized and excluded from social opportunities on a variety of culturally specific grounds. In this collection, the authors explore the impact that the philosophical framing of disability can have on public policy questions, in the clinic, in the courtroom, and elsewhere. They examine the implications of this understanding for legal and policy approaches to disability, strategies for allocating and accessing health care, the implementation of the Americans with Disabilities Act, health care rights, and other legal tools designed to address discrimination. This volume should be read by anyone seeking a balanced view of disability and an understanding of the connection between the framing of disability and policies that have a real-world impact on individuals
Title from publisher's bibliographic system (viewed on 08 Apr 2020)
Disability, Health, and Normal Function / Elizabeth Barnes -- Healthcare as Eugenics / Ani B. Satz -- Epistemic Injustice, Disability Stigma, and Public Health Law / Daniel Goldberg -- Abortion, the Disabilities of Pregnancy, and the Dignity of Risk / Mary Anne Case -- The Down Syndrome Information Act and "Mere Difference :" Redefining the Scope of Prenatal Testing Conversations? / Marie-Eve Lemoine and Vardit Ravitsky -- Dementia, Disability, and Advance Directives : Defensible Legal Standards for Dementia Care / Rebecca Dresser -- Expressing Respect for People with Disabilities in Medical Practice / Adam Cureton -- Disabled Bodies and Good Organs / Emily Largent -- Humanizing Clinical Care for Patients with Disabilities / Omar Sultan Haque and Michael Ashley Stein -- Chronic Pain as a Challenge for Disability Theory and Policy / Caroline J. Huang and David Wasserman -- Making "Meaningful Access" Meaningful : Equitable Healthcare for Divisive Times / Leslie Francis and Anita Silvers -- The Privacy Problem in Disability Antidiscrimination Law / Jasmine E. Harris -- Sexual Agency as a Rights-Based Imperative for Persons with Intellectual Disabilities / Matthew S. Smith, Tara Allison, and Michael Ashley Stein -- Destigmatizing Disability in the Law of Immigration Admissions / Medha D. Makhlouf -- The Normative Bases of Medical Civil Rights / Craig Konnoth -- Judicial Representation : Speaking for Others from the Bench / Wendy Salkin -- Can We Universally Accommodate Mental Health and Should We? : A Systematic Review of the Evidence and Ethical Analysis / Nathaniel Z. Counts, C. Taylor Poor, Julie Erickson, Thomas Hart, and Kelly A. Davis -- Algorithmic Disability Discrimination / Mason Marks -- The Pathways Approach to Priority Setting : Considering Quality of Life While Being Fair to Individuals with Disabilities / Govind Persad -- Measuring Health-State Utility via Cured Patients / Nir Eyal
Keywords: People with disabilities; People with disabilities / Legal status, laws, etc